Respuesta :
Answer:
x = 1
y = 1
Step-by-step explanation:
3y - 4 + x = 0
x = -3y + 4
5x + 6y = 11
5(-3y + 4) + 6y = 11
-15y + 20 + 6y = 11
-9y = -9
y = 1
3(1) - 4 + x = 0
x = 4 - 3
x = 1
Answer:
(1, 1)
Step-by-step explanation:
Given system of linear equations:
[tex]\begin{cases}3y-4+x=0\\5x+6y=11\end{cases}[/tex]
Rewrite the first equation to make x the subject:
[tex]\implies 3y-4+x=0[/tex]
[tex]\implies 3y-4+x+4=0+4[/tex]
[tex]\implies 3y+x=4[/tex]
[tex]\implies 3y+x-3y=4=3y[/tex]
[tex]\implies x=4-3y[/tex]
Substitute the expression for x into the second equation and solve for y:
[tex]\implies 5(4-3y)+6y=11[/tex]
[tex]\implies 20-15y+6y=11[/tex]
[tex]\implies 20-9y=11[/tex]
[tex]\implies 20-9y-20=11-20[/tex]
[tex]\implies -9y=-9[/tex]
[tex]\implies -9y \div -9=-9 \div -9[/tex]
[tex]\implies y=1[/tex]
Substitute the found value of y into the rearranged first equation and solve of x:
[tex]\implies x=4-3(1)[/tex]
[tex]\implies x=4-3[/tex]
[tex]\implies x=1[/tex]
Therefore, the solution to the system of equations is (1, 1).
Learn more about systems of equations here:
https://brainly.com/question/27520807
https://brainly.com/question/28164947